THE JUDICIAL REVIEW AND SEPARATION OF POWERS IN INDONESIA MODERN CHALLENGES FOR CONSTITUTIONAL GOVERNANCE - Dwi Saleha (PLEDOI (Jurnal Hukum dan Keadilan), 2026)
Indonesia, as a developing democracy, faces significant challenges in implementing the principles of judicial review and separation of powers. This article analyzes the dynamics of Indonesia’s constitutional governance in the post-Reformasi era, focusing on the role of the Constitutional Court, the relationships among the legislative, executive, and judicial branches, and the impacts of political modernization and digitalization. Using a qualitative approach based on normative legal analysis and literature review, the article highlights contemporary challenges in ensuring the balance of powers and the protection of constitutional rights. The findings indicate that, although judicial review mechanisms strengthen constitutional supremacy, practical obstacles remain, including political pressure, divergent legal interpretations, and the need for regulatory updates to address the digital era. The article provides strategic recommendations for enhancing constitutional governance in Indonesia.